Analysis on Acceleration of Development in Sumenep Regency Within the Perspective of Human Development - Erlita Cahyasari (Wacana Journal of Social and Humanity Studies, 2018)
In order to improve community’s welfare, the government of Sumenep Regency seeks to do sustainable development. The acceleration of development carried out gives emphasis on human development. There are three indicators in human development; they are (1) longevity, which consists of Life Expectancy of Birth and Infant Mortality Rate; (2) educational achievement, which includes Adult Literacy Rate and the Mean Years of Schooling, and (3) access to resources, which includes Gross Regional Domestic Product. This writing aims to describe and analyze the acceleration of development in Sumenep Regency within the perspective of human development. This research uses descriptive method with secondary data. Results of the study indicate that the indicators (longevity, educational achievement, and access to resources) experience increases and decreases during the period of 2010 and 2016.